Suitability assessment for handling methods of municipal solid waste - B. Seng; T. Fujiwara; B. Seng (Global Journal of Environmental Science and Management)
Solid waste management is challenging in Phnom Penh city, Capital of Cambodia. The only one formal treatment taken is the final disposal of mixed waste into an open dumpsite. The current study analyses the physical and chemical characteristics of municipal solid waste disposed of in the dumpsite to assess their suitable handling methods. The current study found that the major compositions of waste are food waste (49.18%) and plastic (21.13%), and recyclable waste shares about 17.28% of the total. On average, it contains 60.92% moisture, 35.89% combustible, 3.19% ash, 58.32% carbon and 1.05% nitrogen. High calorific value is 10.03 MJ/kg when the low calorific value is 7.77 MJ/kg. The moisture content is too high to meet the technology demands, especially in the rainy season. It seems workable for incineration without energy recovery. Gasification for melting and incineration with energy recovery are only suitable for the dry season. If the solid waste is well pre-separated, material recovery could be one of the suitable handling methods. Food waste, wood and leave could be digested in the one-stage continuous wet system and co-composted, and plastic is appropriate for refuse-derived fuel generation. The current study recommends that the waste pre-separation should be requisite for any handling methods.